UNSUR INTRINSIK PADA NASKAH FILM SERIAL SAIYO SAKATO EPISODE 1 - Rahmania, Eka; Rohimi, Primi (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
This study analyzes the streaming series film script Saiyo Sakato written by Gina S. Noer. This research used a qualitative descriptive method with a structural approach. This comedy drama set in the intrigue of two families united by Padang cuisine raises the issue of patriarchal culture, especially the issue of polygamy which is spiced with various things that are very attached to everyday life. By analyzing intrinsic elements such as theme, character, plot, setting, language style, and message, it was found that the main characters, Uni Mar, Nita, and Annisa, face an inner dilemma between hope and reality and personal achievement or desire and pressure from patriarchal culture in their families. The storyline tells their emotional and mental journey in adjusting to the presence of a new person in their family. This study emphasizes the intrinsic elements contained in the Saiyo Sakato drama script. The structural method helps explain the elements in the drama script, providing a deeper understanding of the meaning and message of this literary work.